An Institutional Perspective on the Employment Position of Temporary Workers in the Netherlands - de Jong, Jeroen; Schalk, René; Goessling, Tobias (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2007)
This article analyzes the complex employment position of temporary workers within organizations and on the labour market. Temporary employment is usually considered secondary to permanent employment. In recent years, the European Union and the Dutch government have attempted to change this situation by formulating several directives and labour laws. In this paper, we use institutional theory to discuss the institutional foundations and influences that shape the employment and labour-market conditions of temporary workers. The analysis shows that the core issues regarding temporary employment conditions include conflicting (legitimate) interests, socially constructed norms that favour permanent workers, and an uneven distribution of power. Our analysis further shows that institutional forces generate a structural justification for the disadvantaged position of temporary workers.